DYSLIPIDEMIA FEATURES IN CHILDREN - T. I. Turkinа; M. Yu. Shcherbakova (Столичная издательская компания, 2016)
Contemporary scientific and practical data about various lipid metabolism disorders (dyslipidemia) in children are discussed. Spectra lipids, phospholipids and lipoproteins in blood serum and erythrocyte membranes are presented. Characteristics of dyslipidemia and hypolipidemia, classification of hyperlipidemia, a description of acetonemic vomiting syndrome are given. Basic principles of dyslipidemia treatment as well as therapy of obesity associated with dyslipidemia are described.